Therapeutic Benefits of Adropin in Aged Mice After Transient Ischemic Stroke via Reduction of Blood-Brain Barrier Damage. Issue 1 (28th October 2022) - Yang, Changjun; Liu, Lei; Lavayen, Bianca P.; Larochelle, Jonathan; Gunraj, Rachel E.; Butler, Andrew A.; Candelario-Jalil, Eduardo
Abstract : Background: Adropin is a peptide encoded by the energy homeostasis-associated gene ( Enho ) that is highly expressed in the brain. Aging and stroke are associated with reduced adropin levels in the brain and plasma. We showed that treatment with synthetic adropin provides long-lasting neuroprotection in permanent ischemic stroke. However, it is unknown whether the protective effects of adropin are observed in aged animals following cerebral ischemia/reperfusion. We hypothesized that adropin provides neuroprotection in aged mice subjected to transient middle cerebral artery occlusion. Methods: Aged (18–24 months old) male mice were subjected to 30 minutes of middle cerebral artery occlusion followed by 48 hours or 14 days of reperfusion. Sensorimotor (weight grip test and open field) and cognitive tests (Y-maze and novel object recognition) were performed at defined time points. Infarct volume was quantified by 2, 3, 5-triphenyltetrazolium chloride staining at 48 hours or Cresyl violet staining at 14 days post–middle cerebral artery occlusion. Blood-brain barrier damage, tight junction proteins, and MMP-9 (matrix metalloproteinase-9) were assessed 48 hours after middle cerebral artery occlusion by ELISA and Western blots. Results: Genetic deletion of Enho significantly increased infarct volume and worsened neurological function, whereas overexpression of adropin dramatically reduced stroke volume compared to wild-type controls. Postischemic treatment with synthetic adropin peptide given at the onset of reperfusion markedly reduced infarct volume, brain edema, and significantly improved locomotor function and muscular strength at 48 hours. Delayed adropin treatment (4 hours after the stroke onset) reduced body weight loss, infarct volume, and muscular strength dysfunction, and improved long-term cognitive function. Postischemic adropin treatment significantly reduced blood-brain barrier damage. This effect was associated with reduced MMP-9 and preservation of tight junction proteins by adropin treatment. Conclusions: These data unveil a promising neuroprotective role of adropin in the aged brain after transient ischemic stroke via reducing neurovascular damage. These findings suggest that poststroke adropin therapy is a potential strategy to minimize brain injury and improve functional recovery in ischemic stroke patients.